2017
DOI: 10.1007/s11356-017-0315-5
|View full text |Cite
|
Sign up to set email alerts
|

The conformation-independent QSPR approach for predicting the oxidation rate constant of water micropollutants

Abstract: In advanced water treatment processes, the degradation efficiency of contaminants depends on the reactivity of the hydroxyl radical toward a target micropollutant. The present study predicts the hydroxyl radical rate constant in water (k ) for 118 emerging micropollutants, by means of quantitative structure-property relationships (QSPR). The conformation-independent QSPR approach is employed, together with a large number of 15,251 molecular descriptors derived with the PaDEL, Epi Suite, and Mold2 freewares. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Only a handful of prediction trials were reported using a limited number of variations of reaction conditions. [1,2] On the other hand, reaction rate constants, [3][4][5][6] equilibrium constants [7] and enantioselectivity, [8][9][10] which are associated with energy differences, have been the main targets for predictive models. These parameters can be predicted from the independent variables which are numerically representable and are assumed to be important for the target reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Only a handful of prediction trials were reported using a limited number of variations of reaction conditions. [1,2] On the other hand, reaction rate constants, [3][4][5][6] equilibrium constants [7] and enantioselectivity, [8][9][10] which are associated with energy differences, have been the main targets for predictive models. These parameters can be predicted from the independent variables which are numerically representable and are assumed to be important for the target reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The log K values predicted with optimal SVM model are listed in Table and sketched in Figure 1. The training and test sets have coefficients of determination R 2 of 0.923 and 0.925, respectively, which are higher than those ( R 2 = 0.584–0.918) in the models (Borhani et al, 2016; Gupta & Basant, 2017; Jin et al, 2015; Luo et al, 2017; Ortiz et al, 2017; Sudhakaran & Amy, 2013; Toropov et al, 2012; Wols & Vries, 2012), although these models dealt with relatively small data sets of the reaction rate constants log k OH between •OH and organic compounds in aqueous phase.…”
Section: Resultsmentioning
confidence: 85%
“…Recently, Ortiz et al (2017) employed five descriptors to obtain a MLR model for log k OH of 118 organic compounds. The MLR model was obtained from a training set (89 compounds) and validated with a test set (29 compounds).…”
Section: Introductionmentioning
confidence: 99%
“…They were catalogued from the Supporting Information from ref. Zhong et al, Borhani et al, Ortiz et al, Xiao et al, Wojnárovits and Takács the IscoKin, and NIST database. The kinetic parameters are catalogued under standard conditions, 25 °C and 1 mol·L –1 in the aqueous phase.…”
Section: Methodsmentioning
confidence: 99%